Russian Attempts on Constitutional Issue of Insurgent Serbia - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The second attempt at constitutional organization, called Osnovanije Praviteljstva Sebskago (Establishment of a Serbian Government), was made by Constantine Constantinovich Rodofinikin, a Russian representative of Greek origine, immediatly after his arrival in Serbia (August 2, 1807). It was signed by Karađorđe on August 20, 1807. According to this project, the supreme power in liberated Serbia was to be executed by the Praviteljstvujušči Senat, i.e. a governing senate, composed of three categories of members: military commanders (vojvode), former honorable members of the council (sovjet) and elected representatives of the nahiyes (Turkish districts or counties). The first two categories were to be nobles with a lifelong membership in the senate, while the members of the third category were able to achieve nobility only if elected three times into the senate. Karađorđe was to preside over the senate, bearing the title of svetlejši knez, „sublime prince,“ who would have the right of three votes. Rodofinikin did not consider Karađorđe to be an appropriate person to collaborate with. As a leader of the Uprising, responsible for its military success, Karađorđe demanded urgent, concrete and conditionless Russian aid. On the other hand, Karađorđe wanted autonomous and apsolutic power. Rodofinikin in his Establishment of a Serbian Government, gave him only the presidency over the Senate and the right of three votes. According to this Act, Karađorđe’s power was neither hereditary, nor for a lifetime. Karađorđe was not at all satisfied with Rodofinikin’s document, but he agreed to the Act thinking that it was the necessary price for Russian support.The aim of Rodofinikin, as well as Paulucci, was to ensure Russian influence in Serbia. However, Paulucci wanted to place Russian officers in all of the governing and commanding positions, while Rodofinikin’s desire was to create some kind of Serbian aristocracy, faithful to Russia. During his entire stay in Serbia (August 2, 1807 – August 15, 1809) he supported Karađorđe’s opponents, promissing them different favours and trying to limit the absolutic power of Serbian Vožd. Such a policy, filled with intrigues and plots, brought much more harm not only to Karađorđe and insurgent Serbia, but to Rodofinikin himself and to Russian policy as well.However, Rodofinikin’s project did not come into force, as the Russian Tsar, due to the political situation, did not approve of it.